Distinct and overlapping functions of Miscanthus sinensis MYB transcription factors SCM1 and MYB103 in lignin biosynthesis - Golfier, Philippe; Ermakova, Olga; Unda, Faride; Murphy, Emily K.; Xie, Jianbo; He, Feng; Zhang, Wan; Lohmann, Jan U.; Mansfield, Shawn D.; Rausch, Thomas; Wolf, Sebastian (International journal of molecular sciences, 2021)
Cell wall recalcitrance is a major constraint for the exploitation of lignocellulosic biomass as a renewable resource for energy and bio-based products. Transcriptional regulators of the lignin biosynthetic pathway represent promising targets for tailoring lignin content and composition in plant secondary cell walls. However, knowledge about the transcriptional regulation of lignin biosynthesis in lignocellulosic feedstocks, such as Miscanthus, is limited. In Miscanthus leaves, MsSCM1 and MsMYB103 are expressed at growth stages associated with lignification. The ectopic expression of MsSCM1 and MsMYB103 in N. benthamiana leaves was sufficient to trigger secondary cell wall deposition with distinct sugar and lignin compositions. Moreover, RNA-seq analysis revealed that the transcriptional responses to MsSCM1 and MsMYB103 overexpression showed an extensive overlap with the response to the NAC master transcription factor MsSND1, but were distinct from each other, underscoring the inherent complexity of secondary cell wall formation. Furthermore, conserved and previously described promoter elements as well as novel and specific motifs could be identified from the target genes of the three transcription factors. Together, MsSCM1 and MsMYB103 represent interesting targets for manipulations of lignin content and composition in Miscanthus towards a tailored biomass.
Gesehen am 07.01.2022